Édito - Hors les murs. Enseigner et apprendre à l’épreuve de la « continuité pédagogique » - Hélène Buisson-Fenet; Lisa Marx (Recherches en Éducation)
Lockdown paradoxically reveals the characteristics and usual functioning of the educational system: the despatialization and detemporalization of education sheds a new light on practices, identities and regulations that are otherwise too ordinary and routine to be conceptualized. "Educational continuity" has come to signify both a moral injunction (teaching must not be interrupted) and a technical imperative (teaching must be adapted to not only prevent learning loss but to advance learning). The dossier in this issue of Recherches en éducation focuses on how this injunction has been seized upon and shows a complex and nuanced reality featuring practices that precede lockdown but which have become more prominent. Articles focus both on the institutional side or professional groups and the side of pupils, students and families and cover different levels, ranging from kindergarten to university.